Echocardiographic diagnosis of a large coronary artery fistula in a newborn. Issue 10 (20th September 2022) - Masci, Marco; Moras, Patrizio; Campanale, Cosimo Marco; Guk, Yeva; Donato, Valeria; Toscano, Alessandra
Abstract: Coronary artery fistula (CAF) is a rare cause of heart murmur in newborns, with a very heterogeneous clinical presentation and unpredictable natural history. We described the case of a large neonatal CAF in an asymptomatic newborn. The patient did not show any symptoms of heart failure during a three‐month follow‐up. In this case, echocardiography was as accurate as CT scan in describing the anatomy and the course of CAF.